O blog no ensino de estudos amazônicos: materiais didáticos em questão - OLIVEIRA, Leonardo da Costa (Universidade Federal do Pará, 2023)
This master's thesis aims to analyze the access forms of EMEF João Paulo II teachers to the teaching materials of the curricular component Amazon studies through the absence of a textbook that meets the specificities of the school discipline in question. Also part of the restlessness of the work was the peculiarity of the discipline in it is curricular design, as well as it is interdisciplinary characteristic. It was verified the relevance of the teaching materials used by the teachers in the classes of Amazonian Studies, as well as their strategies of production of them. And as a proposal for mediation for the concerns that motivated the present work, the research presents as a didactic product the blog, here used as a pedagogical resource. Considering the Internet a space made of navigable information circuits and a virtual world of communication that expands indefinitely, both teachers and students of Basic Education, who are connected to the World Computer Network, can be have an opportunity to access teaching materials related to the curricular component Amazonian Studies. To realize the proposed objectives of this dissertation, was chosen from the methodological perspective of the case study in a qualitative approach that uses as an instrument for data collection closed questionnaire, interviews and documentary analysis.